2010
DOI: 10.1002/dvdy.22516
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous activation of SHR and ATHB8 expression defines switch to preprocambial cell state in Arabidopsis leaf development

Abstract: The processes underlying the formation of leaf vascular networks have long captured the attention of developmental biologists, especially because files of elongated vascular-precursor procambial cells seem to differentiate from apparently equivalent, isodiametric ground cells. In Arabidopsis leaves, ground cells that have been specified to vascular fate engage expression of ARABIDOPSIS THALIANA HOMEOBOX8 (ATHB8). While definition of the transcriptional state of ATHB8-expressing ground cells would be particular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
80
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(84 citation statements)
references
References 78 publications
4
80
0
Order By: Relevance
“…Figure 2 shows that OsSHR2 transcripts accumulate in developing veins of plastochron P2 to P4 rice leaf primordia (where a plastochron is the time interval between the initiation of leaf primordia, and P1 is the youngest and closest to the shoot meristem from which the leaves are derived). In contrast to Arabidopsis, where AtSHR transcripts accumulate in procambium and persist throughout vascular development (Dhondt et al, 2010;Gardiner et al, 2011;Cui et al, 2014), OsSHR2 transcripts are detectable only in veins after the surrounding bundle sheath cells have differentiated, and then expression is relatively short-lived (Fig. 2C).…”
Section: Duplicate Shr Genes In Grassesmentioning
confidence: 92%
“…Figure 2 shows that OsSHR2 transcripts accumulate in developing veins of plastochron P2 to P4 rice leaf primordia (where a plastochron is the time interval between the initiation of leaf primordia, and P1 is the youngest and closest to the shoot meristem from which the leaves are derived). In contrast to Arabidopsis, where AtSHR transcripts accumulate in procambium and persist throughout vascular development (Dhondt et al, 2010;Gardiner et al, 2011;Cui et al, 2014), OsSHR2 transcripts are detectable only in veins after the surrounding bundle sheath cells have differentiated, and then expression is relatively short-lived (Fig. 2C).…”
Section: Duplicate Shr Genes In Grassesmentioning
confidence: 92%
“…The degree of reduction of luminal area accounted for smaller diameters of mutant hypocotyls, indicating that KNAT1 and STM were required for early steps of xylem cell differentiation. We then examined expression patterns of ATHB8, an early marker of vascularization that, when overexpressed, promotes xylem fiber and vessel differentiation (Baima et al, 1995;Gardiner et al, 2011). In wild type, pAtHB8::GUS was expressed in the cambium and developing xylem, peaking in cell files, which give rise to xylem vessel cells, and to a lesser extent in cells at the origin of fiber cell files.…”
Section: Knat1mentioning
confidence: 99%
“…The preferential expression of SHR direct targets in the xylem and pericycle suggests a direct role for SHR in the specification of these cell types. A role for SHR in xylem and phloem differentiation has been identified (Carlsbecker et al, 2010;Gardiner et al, 2011;Yu et al, 2010), but whether SHR has a role in pericycle specification is unclear, so we examined the effect of the shr mutation on pericycle cell fate using the pericycle markers J0121 (Laplaze et al, 2005) and S17 (Lee et al, 2006). In wild-type root, J0121 was first detected in the early elongation zone, but in shr, it was not detected until late into the maturation zone (Fig.…”
Section: Clustering Analysis Revealed a Direct Role For Shr In Vasculmentioning
confidence: 99%
“…Levesque et al (2006) first noted that in shr the number of cell files in the stele was reduced. Subsequently, several studies showed that SHR has a role in promoting vascular tissue differentiation and lateral root formation (Carlsbecker et al, 2010;Gardiner et al, 2011;Yu et al, 2010). Carlsbecker et al (2010) showed that the shr mutation causes the loss of protoxylem.…”
mentioning
confidence: 99%